2000
DOI: 10.4049/jimmunol.165.2.1123
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR-Promiscuous T Cell Epitopes fromPlasmodiumfalciparumPre-Erythrocytic-Stage Antigens Restricted by Multiple HLA Class II Alleles

Abstract: Previously, we identified and established the antigenicity of 17 CD8+ T cell epitopes from five P. falciparum Ags that are restricted by multiple common HLA class I alleles. Here, we report the identification of 11 peptides from the same Ags, cicumsporozoite protein, sporozoite surface protein 2, exported protein-1, and liver-stage Ag-1, that bind between at least five and up to 11 different HLA-DR molecules representative of the most common HLA-DR Ags worldwide. These peptides recall lymphoproliferative and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
105
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 56 publications
11
105
0
Order By: Relevance
“…We have previously reported induction of antigen-specific, CD8 ϩ T cell-dependent, genetically restricted, class I-restricted CTL against the same peptides after DNA immunization (5). However, based on murine studies, we concluded that class I-restricted IFN-␥ responses are the primary immune effectors contributing to the long-lasting, preerythrocytic stage-specific protection of mice and humans after immunization with irradiated sporozoites (7,20). Data presented here establish that these responses can be induced in humans by plasmid DNA expressing the PfCSP.…”
Section: Discussionmentioning
confidence: 67%
“…We have previously reported induction of antigen-specific, CD8 ϩ T cell-dependent, genetically restricted, class I-restricted CTL against the same peptides after DNA immunization (5). However, based on murine studies, we concluded that class I-restricted IFN-␥ responses are the primary immune effectors contributing to the long-lasting, preerythrocytic stage-specific protection of mice and humans after immunization with irradiated sporozoites (7,20). Data presented here establish that these responses can be induced in humans by plasmid DNA expressing the PfCSP.…”
Section: Discussionmentioning
confidence: 67%
“…5 More recently, it has been reported that some of these pre-erythrocytic stage antigens also contain HLA-DR CD4 + T cell epitopes restricted by multiple HLA class II supertype alleles. 33 Interestingly, a high degree of overlap has been noted between the promiscuous class II CD4 + T cell epitopes reported recently and the degenerate class I CD8 + epitopes identified previously. 5,33 Therefore, we speculate that both CD8 + and CD4 + T cells could respond to some of pre-erythrocytic stage antigens to produce the IFN-␥ observed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Peptides that are capable of binding to the majority of the most common molecules of a given supertype can be identified by in vitro peptide-MHC binding assays, and are designated as supertype binding peptides. A correlation between immunogenicity and the capacity to bind multiple molecules from a given HLA supertype has been documented in several studies (21)(22)(23)(24)(25), and high-affinity binding to the prototype allele of a given supertype has been shown to be highly predictive of supertype binding (17). Herein, we examined whether predictions based on prototype alleles could efficiently identify supertype binders.…”
Section: Resultsmentioning
confidence: 97%
“…Herein, we examined whether predictions based on prototype alleles could efficiently identify supertype binders. Accordingly, we analyzed Mage2͞3, hepatitis B virus, hepatitis C virus, and Plasmodium protein sequences to examine how many of the previously identified supertype binders (15,(21)(22)(23)(24)(25)(26) were identified by our predictive algorithms (100 nM was selected as the threshold predictive value; Fig. 2).…”
Section: Resultsmentioning
confidence: 99%